Exploring EFL literature approaches in Dutch secondary education. Issue 2 (3rd May 2016) - Bloemert, Jasmijn; Jansen, Ellen; van de Grift, Wim
ABSTRACT: There is an increasing awareness that the inclusion of literature in foreign language (FL) curricula can be beneficial to language learners. Especially, the move towards integrated language and literature curricula is gaining ground. In this study we investigated the way English as a foreign language (EFL) is approached in Dutch secondary education at pre-university level. Using a survey study ( N = 106 EFL teachers), we investigated (1) how EFL teachers approach literature at pre-university level in Dutch secondary education and also (2) which factors are related to the reported occurrence of four FL literary teaching approaches. Confirmatory factor analysis shows that the four identified approaches represent one underlying construct, which underlines our understanding of a Comprehensive Approach to FL literature teaching. Results indicate that the variation between the ways FL teachers approach literature is enormous. Correlation analyses and t -tests informed us that curricular factors are significantly related to the way literature is approached. The fact that teacher demographics are generally not significantly related to the way FL literature is approached could be ascribed to curricular heritage or the way FL literature curricula are designed. The study concludes by suggesting several directions for future research.